Light‐Controlled Precise Delivery of NIR‐Responsive Semiconducting Polymer Nanoparticles with Promoted Vascular Permeability. Issue 19 (26th July 2021) - Qi, Weizhi; Li, Tingting; Zhang, Chen; Liu, Fei; Wang, Jun; Chen, Dandan; Fang, Xiaofeng; Wu, Changfeng; Li, Kai; Xi, Lei
Abstract: The endothelial barrier plays an essential role in health and disease by protecting organs from toxins while allowing nutrients to access the circulation. However, it is the major obstacle that limits the delivery of therapeutic drugs to the diseased tissue. Here, it is reported for the first time that near‐infrared (NIR) laser pulses can transiently promote the delivery of semiconducting polymer nanoparticles passing the vascular barrier via photoacoustic‐effect‐induced accumulation, only by the aid of pulse laser irradiation. This strategy enables selective and substantial accumulation of the NIR‐absorbing nanoparticles inside specific tissues, implying the discovery of an unprecedented approach for light‐controlled nanoparticle delivery. Especially, the nanoparticle delivery in solid tumors by 10‐min laser scanning is approximately six times higher than that of the enhanced permeability and retention (EPR) effect in 24 h under current experimental conditions. Further results confirm that this strategy facilitates substantial accumulation of nanoparticles in the mouse brain with intact skull. This approach thus opens a new door for tissue‐specific delivery of nanomaterials with an unprecedented level of efficiency and precision. Abstract : In this study, it is shown that near‐infrared light can open vascular barrier via photoacoustic‐induced accumulation, enabling substantial accumulation of semiconducting polymer nanoparticles in specific tissues that are exposed to the light irradiation. It is elucidated that the barrier opening is a selective and transient process, which opens a new door for advanced nanomedicine delivery.